2020
DOI: 10.1016/j.cell.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Converting Escherichia coli to a Synthetic Methylotroph Growing Solely on Methanol

Abstract: Highlights d E. coli was engineered to grow on methanol alone by rational design and evolution d A doubling time of 8.5 h and maximum OD of 2 were achieved d Formaldehyde-induced DNA-protein crosslinking was identified and solved d Copy number variation of a region spanning 70kb facilitates carbon source shifts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(180 citation statements)
references
References 40 publications
(52 reference statements)
2
161
2
Order By: Relevance
“…Autonomous synthetic methylotrophy, wherein growth on methane or methanol does not require additional carbon sources, has been difficult to realize. Only one study to date has reported the successful construction of a true E. coli methylotroph (Chen et al, 2020). In order to achieve this feat, the authors relied on a combination of rational engineering and adaptive laboratory evolution (ALE).…”
Section: Introductionmentioning
confidence: 99%
“…Autonomous synthetic methylotrophy, wherein growth on methane or methanol does not require additional carbon sources, has been difficult to realize. Only one study to date has reported the successful construction of a true E. coli methylotroph (Chen et al, 2020). In order to achieve this feat, the authors relied on a combination of rational engineering and adaptive laboratory evolution (ALE).…”
Section: Introductionmentioning
confidence: 99%
“…The ability for EfgA to provide an immediate benefit in dealing with formaldehyde stress may also have more immediate biotechnological benefits. Given that formaldehyde toxicity was also a key challenge in the engineering and evolution of an E. coli strain that can grow on methanol as a sole carbon source [128], this raises the possibility that introducing EfgA would increase the cells’ ability to grow while producing formaldehyde as a high flux intermediate. We perhaps should not be surprised that metabolic pathways that generate toxic intermediates need molecular systems to sense their accumulation and mount responses that either eliminate the toxin, increase the ability to repair such damage, or help the cell avoid making the molecules that the toxin damages in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…The ability for EfgA to provide an immediate benefit in dealing with formaldehyde stress may also have more immediate biotechnological benefits. Given that formaldehyde toxicity was also a key challenge in the engineering and evolution of an E. coli strain that can grow on methanol as a sole carbon source [132], this raises the possibility that introducing EfgA would increase the cells' ability to grow while producing formaldehyde as a high-flux intermediate. We perhaps should not be surprised that metabolic pathways that generate toxic intermediates need molecular systems to sense their accumulation and mount responses that either eliminate the toxin, increase the ability to repair such damage, or help the cell avoid making the molecules that the toxin damages in the first place.…”
Section: Plos Biologymentioning
confidence: 99%